DReaM - Språkbanken Text (University of Gothenburg, 2024)
This resource contains an openly available multilingual digitized version of thousands of documents describing natural languages of the world. The corpus is annotated with various meta, word, and text level attributes. More details
about the data and annotations can be found in the reference given below.

There is also a password protected part of the corpus which can be found here.

Standard reference:
{publication 295338}

Den öppna och fritt tillgängliga delen av DReaM-korpusen är en samlingen med tusentals flerspråkiga digitala dokument som beskriver världens språk. Dokumenten är berikade med metadata och språkteknologiska analyser. För mer information
hänvisar vi till publikationen som anges nedan, som även är samlingens standardreferens.

Det finns också en lösenordsskyddad del av korpusen som kan hittas här.

Standard reference:
{publication 295338}
DReaM
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik